2016
DOI: 10.5222/buchd.2016.073
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological frequency of Helicobacter pylori in children between 1-18 ages in the Erzurum province

Abstract: Erzurum ilinde endoskopik biyopsilerde pediatrik yaş grubunda HP sıklığı %61,01'dir. Bir-beş yaş arası çocuklarda HP sıklığı %57,14 oranında saptanmış olup ülkemizin batısında ve Batı ülkelerinde yapılan çalışmalara göre daha yüksek bulunmuştur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The rates of atrophy and intestinal metaplasia in gastric endoscopic biopsy specimens vary in studies. In the study by Erdoğan Durmuş et al, 37 atrophy and intestinal metaplasia were not observed. In contrast, in the study by Marginean et al, 38 atrophy was observed in 3 and intestinal metaplasia in 4 of 462 cases.…”
Section: Discussionmentioning
confidence: 84%
“…The rates of atrophy and intestinal metaplasia in gastric endoscopic biopsy specimens vary in studies. In the study by Erdoğan Durmuş et al, 37 atrophy and intestinal metaplasia were not observed. In contrast, in the study by Marginean et al, 38 atrophy was observed in 3 and intestinal metaplasia in 4 of 462 cases.…”
Section: Discussionmentioning
confidence: 84%